Curriculum Reform in Practice: Implementation of Kurikulum Merdeka in Islamic Religious Education at Sekolah Penggerak - Ummul Khair; Hendra Harmi; Dewi Purnama Sari (AL-ISHLAH: Jurnal Pendidikan, 2026)
The Merdeka Curriculum is an Indonesian curriculum reform intended to increase school and teacher autonomy and to strengthen competency- and character-based learning. However, evidence on how this curriculum is enacted in Islamic Religious Education (Pendidikan Agama Islam/PAI) at the elementary level remains limited. This study examined the implementation of PAI under the Merdeka Curriculum in a Sekolah Penggerak (Driving School) context at SD Negeri 02 Rejang Lebong. Using a qualitative descriptive case study design, data were collected from July to December 2024 through classroom observations, semi-structured interviews with four PAI teachers, the school principal, and selected students, and analysis of instructional documents (modules and lesson plans). Data were analyzed thematically following Braun and Clarke, supported by triangulation and member checking to enhance credibility. Findings indicate that teachers used increased curricular flexibility to prioritize essential and contextual PAI content based on initial diagnostic assessment and clearly stated learning objectives. Instruction commonly incorporated discussion, interactive explanation, reflective questioning, role play, Qur’anic reading practice, and value-based projects (e.g., charity and community service) to connect religious concepts with students’ lived experiences. Assessment emphasized continuous formative feedback through quizzes, portfolios, performance tasks, and observation of value enactment in daily behavior; remedial and enrichment activities were applied according to student needs. A recurring challenge concerned uneven parental support for reinforcing religious values at home. Overall, Merdeka Curriculum enactment in PAI fostered a student-centered and value-oriented learning environment that supported both understanding of Islamic teachings and character development, while highlighting the need for stronger school–family collaboration.